No better friend : a man, a dog, and their incredible true story of friendship and survival in World War II - Weintraub, Robert (Little, Brown and Company, 2018)
Explores the true story of Frank Williams, an air force technician, and Judy, a purebred pointer, who met in a POW camp during World War II. Frank and Judy bonded together to survive and inspire fellow prisoners in the camp.